(untitled) (Journal of Global Accounting, 2022)
The study examines the effect of stamp duty tax on economic growth in Nigeria. Ex Post Facto research design was adopted for the study. Data for the study were extracted from the Statistical Bulletin and Bureau of National Statistics and Central Bank of Nigeria from 2000 to 2020. The statistical package used to run the regression is STATA 16. The result revealed that stamp duty has a negative but significant effect on economic growth in Nigeria. Hence, the study concludes that higher stamp duty tax revenue surprisingly stalled economic growth in Nigeria during the period. This study recommends that government should improve public entities and provide strong government investment which should be used as a source of domestic revenue generated from different business activities.